Radioimmunotherapy: future prospects from the perspective of brachytherapy - Fleischmann, Maximilian; Glatzer, Markus; Rödel, Claus; Tselis, Nikolaos (Journal of Contemporary Brachytherapy, 2021)
In combination with radiotherapy, immunotherapy is becoming an increasingly used strategy in treating advanced, recurrent, or metastatic cancer. The evident impact of radiotherapy on local and systemic immune response is an indication of the synergistic effect of these two modalities. There is a strong rationale to combine radiotherapy and immunotherapy to enhance response rates and overcome resistances. Therefore, the combination of radio- and immunotherapy holds a variety of opportunities as well as challenges in treating primary cancer and is progressively tested in curative settings. Brachytherapy is also known as internal radiation therapy and only offers a local therapy option at first glance: due to tumor-specific antigens, released by a high local radiation dose, a systemic immune response could be plausible and eminent. Accordingly, brachytherapy could be an underestimated partner with immuno-therapeutic approaches in both curative and palliative settings, to generate local and systemic response. In this review, we summarized the potential benefit of a potential combination of brachytherapy and immuno-therapeutic approaches vs. the background of limited data.